Targeted and untargeted metabolomics applied to occupational exposure to hyperbaric atmosphere. (1st August 2020) - Tranfo, Giovanna; Marchetti, Enrico; Pigini, Daniela; Miccheli, Alfredo; Spagnoli, Mariangela; Sciubba, Fabio; Conta, Giorgia; Tomassini, Alberta; Fattorini, Luigi
Highlights: Six divers were monitored during two experiments of exposure to hyperbaric atmosphere in dry and wet conditions 30 minutes at 3 atmospheres increased the urinary excretion of 8-oxoGuo and 8-oxodGuo after 1.5 hours in dry and 4 hours in wet conditions The levels of 8-oxoGuo and 8-oxodGuo tend to return to the baseline after 12 hours NMR untargeted profiling of urine has individuate some statistically significant differences between Dry and Wet sessions NMR shows that Hypoxanthine level increases during the wet exposure similarly to those of 8-oxoGuo and 8-oxodGuo Abstract: Occupational exposure to hyperbaric atmosphere occurs in workers who carry out their activity in environments where breathing air pressure is at least 10% higher than pressure at sea level, and operations can be divided in Dry or Wet activities. The increased air pressure implies the formation of reactive oxygen species (ROS) and reactive nitrogen species (RNS), consumption of antioxidants and reduction of antioxidant enzyme activity, causing lipid peroxidation, DNA and RNA damage. The present study was aimed to establish the relation between hyperbaric exposure and metabolic changes due to ROS unbalance, by means of the determination of urinary biomarkers of oxidatively generated damage to DNA and RNA during a controlled diving session. The investigated biomarkers were 8-oxo-7, 8-dihydroguanine (8-oxoGua), 8-oxo-7, 8-dihydroguanosine (8-oxoGuo), and 8-oxo-7, 8-dihydro-2'-deoxyguanosine (8-oxodGuo). The experimental session involved six experienced divers subjected to 3 atmospheres absolute for 30 minutes in two different experiments, in both dry and wet conditions. Urine samples were collected at t = 0 (before exposure) and 30 (end of exposure), 90, 240, 480 and 720 minutes. The concentration of 8-oxoGua, 8-oxoGuo, and 8-oxodGuo was determined by isotopic dilution high performance liquid chromatography (HPLC-MS/MS). In all subjects there is an increase of the urinary excretion of 8oxo-Guo and 8oxo-dGuo, in both conditions, after 1.5 - 4 hours from the start of the experiment, and that the values tend to return to the baseline after 12 hours. Besides that, also the nucleic magnetic resonance (NMR)-based untargeted metabolomics was employed for the same objective on the same samples, confirming a different metabolic response in the subjects exposed to dry or wet conditions. In particular, the observed hypoxanthine urinary level increases during the underwater hyperbaric exposure, in agreement with the trend observed for 8-oxoGuo and 8-oxodGuo levels. Present results confirmed the relationship between exposure and oxidative stress and depicted a clear temporal trend of the investigated biomarkers. Due to the possible negative consequences of oxidative stress on workers, present research shows a new line in term of risk prevention.